DOSA ASAL: BERDASARKAN EKSEGESIS SURAT ROMA 5:12 - 21 - Bartholomeus Diaz Nainggolan (Jurnal Koinonia, 2015)
Because of Jesus, people can enjoy life to the fullest. Because of him,humans have a new chance in life. In contrast to a lot of people who do not knowJesus, man can experience the joy that remains, as it has a guarantee of eternalsalvation. Amid all the pressures and hardships of life, people can be relieved in thelove of God